Some experiments on the flow in the boundary layer of a 45 degrees sweptback untapered wing of aspect ratio 4 - Emslie, K.; Hosking, L.; Marshall, W. S. D. (College of Aeronautics, Cranfield, 1953)
Visual methods have been used together with a yawmeter to illustrate conditions of flow in the boundary layer over a sweptback wing. It was found out that at moderate incidences a marked outflow in the boundary layer was developed. Continues …